7.3.3 Integrating Systems Engineering with Project Management: a Current Challenge!. Issue 1 (July 2014) - Xue, Rui; Baron, Claude; Esteban, Philippe; Prun, Daniel
Abstract With increasingly complex systems, relying on systems engineering as an interdisciplinary method to manage engineering processes is essential for companies. However, too many projects still fail and industrial groups have argued that these failures may be related to the managerial techniques used. Indeed organizational processes are more or less specifically mentioned in System Engineering standards but in practice project managers tend to rely more on their own standards which sometime set forth practices not in line with those of the System Engineering domain, hence the reported discrepancies which very often lead to project failure. Thus to improve the companies' competitiveness when developing new products, cooperation between processes related to system development and project management is key to achieve performance and success. This paper presents arguments which tend to support this theory and details two ongoing projects that aim at integrating both domains.